PENGARUH BEBAN KERJA DENGAN PELAKSANAAN PERILAKU CARING PERAWAT PELAKSANA MENURUT PERSEPSI PASIEN DI RS HUSADA JAKARTA - Saragih, Enni Juliani (Jurnal Kesehatan Holistic, 2017)
High workload in staff nurse would cause fatigue which results in decreased caring behavior. The aim of this study was to determine the relationship between staff nurses` workload and their caring behavior practice based on the clients` perception. This study ussed descriptive correlation study with cross sectional approach involving 35 staff nurses and 35 patients. The result showed that client’s perception on staff nurses’ caring behavior were low (54,2%). Meanwhile, the work load more than the standart optimum productive (80%): the workload of day shift nurses was higher (95,13%) than evening shift (93,45%) and night shift (71,58%). The average workload was 86,2%. From the statistical analysis demonstrated that was a significance relationship between staff nurses’ workload and their caring behavior practice based on the clients’ perception (p value=0.004, ?=0.05). The implications of this study are expected to be the core of caring nursing practice by continuing to improve the teaching and dissemination of the concept of caring in nursing practice through training to nurses who provide nursing care to patients